2021
DOI: 10.1080/13811118.2021.1885534
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Mindfulness, Self-Compassion, and Emotion Regulation in Self-Injury

Abstract: Objective:The objective of the current study was to investigate whether mindfulness and selfcompassion are negatively associated with engagement in non-suicidal self-injury (NSSI) and whether emotion dysregulation would mediate this relation. Method: 343 participants (82.2% female; Mage = 23.98; SD = 7.47) were recruited from university and community settings, and completed online questionnaires. Two groups of participants were created: those with lifetime engagement in NSSI (n = 153) and a comparison group wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
0
18
2
Order By: Relevance
“…However, it is important to note that among university students with low levels of mindfulness, those with high levels of self-compassion made more frequent attempts at NSSI compared to students with low selfcompassion levels. These ndings contradict prior research that suggested self-compassion has a buffering effect, reducing NSSI(Cleare et al, 2019;Per et al, 2022). Conversely, in line with previous research that found no signi cant buffering effect of self-compassion on NSSI(Hasking et al, 2019;Nagy et al, 2021).…”
contrasting
confidence: 86%
See 1 more Smart Citation
“…However, it is important to note that among university students with low levels of mindfulness, those with high levels of self-compassion made more frequent attempts at NSSI compared to students with low selfcompassion levels. These ndings contradict prior research that suggested self-compassion has a buffering effect, reducing NSSI(Cleare et al, 2019;Per et al, 2022). Conversely, in line with previous research that found no signi cant buffering effect of self-compassion on NSSI(Hasking et al, 2019;Nagy et al, 2021).…”
contrasting
confidence: 86%
“…Individuals with higher levels of mindfulness effectively cope depression and anxiety (Brown & Ryan, 2003;Carson & Langer, 2006;Cho, Y. et al, 2014). Those with high levels of mindfulness have reported signi cant reductions in NSSI and suicidal ideation (Per et al, 2022). Additionally, low mindfulness tend to engage in more NSSI behaviors (Heath, Joly & Carsley, 2016).…”
Section: The Disconnection and Rejectionmentioning
confidence: 99%
“…alternative explanation is that participants in the current study were adolescent while participants in other studies were usually adults (Caltabiano & Martin, 2017;Per et al, 2021) which leads to inconsistent results. Moreover, in concordance with prior studies (Borders et al, 2010;Peters et al, 2015;Shorey et al, 2015), the current study authenticated that describing, acting with awareness, and nonjudging were negatively correlated with aggression among adolescents.…”
Section: Discussionmentioning
confidence: 75%
“…Consistent with this hypothesis, Wisener and Khoury (2022) reported that trait mindfulness and self-compassion mediated the relationship between emotional regulation and eating as a coping strategy. Additionally, Per et al (2022) demonstrated that the relationship between emotional regulation and non-suicidal self-injury was mediated by mindfulness and self-coldness (the opposite of selfcompassion). When taken together with the first finding, these results highlight the potential importance of physical, mental, and spiritual influences for improving emotional regulation.…”
Section: Discussionmentioning
confidence: 99%